2021
DOI: 10.24191/apmaj.v16i3-10
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Financial Inclusion in Developing Economies: A Multidimensional Index

Abstract: Financial inclusion is a major policy concern especially in developing economies. However, an established measure of financial inclusion is still absent. This paper aims to fill this gap by measuring and examining the level of financial inclusion in 66 developing economies. A Financial Inclusion Index (FII) was constructed, incorporating five indicators (ATM, Bank, Other Financial Institutions, Deposits and Loans) for 2013 until 2019. Two-staged Factor Analysis was employed for weights assignment. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The results of the first-stage PCA used for FII construction are presented in Table 5. Dimensions extracted for the researched SEE countries, "access" and "usage and availability", are consistent with the dimensions extracted by Borhan et al, (2021).…”
Section: Financial Inclusion Index For Seesupporting
confidence: 74%
See 3 more Smart Citations
“…The results of the first-stage PCA used for FII construction are presented in Table 5. Dimensions extracted for the researched SEE countries, "access" and "usage and availability", are consistent with the dimensions extracted by Borhan et al, (2021).…”
Section: Financial Inclusion Index For Seesupporting
confidence: 74%
“…Based on the previous research and taking into account the availability of data, eight indicators were identified to be included in FII construction. The FII was created according to the methodology used by Sarma (2008Sarma ( , 2010Sarma ( , 2012, Amidzic et al (2014), andBorhan et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grouping is done prior to deploying factor analysis. The majority of researchers (Sarma 2008, Sarma 2012, Amidzic, et al 2014, Sarma 2016, Camara & Tuesta (2018, Goel & Sharma (2017) Park & Mercado (2018), Nguyen, (2021) use three dimensions: access (or penetration), availability and usage, Borhan et al, (2021) use two dimensions (access and usage) while Gupte, et al (2012) use as many as four: outreach (penetration and accessibility), usage, ease of transactions, and cost of transactions. Camara & Tuesta, (2018) even introduce the barriers dimension.…”
Section: Literature Review On Financial Inclusion Measurementmentioning
confidence: 99%